PROFIL SELF-CONCEPT AKADEMIK MAHASISWA BARU PROGRAM STUDI BIMBINGAN DAN KONSELING - Siti Muyana (JURNAL KONSELING GUSJIGANG, 2017)
This study aims to determine the condition of academic self-concept of new students Study Program Guidance and Counseling Universitas Ahmad Dahlan. This research is a kind of quantitative research with descriptive method. The instrument used in this research is academic self-concept scale. Subjects in this study amounted to 53 students of Study Program Guidance and Counseling Universitas Ahmad Dahlan taken by using purposive sampling technique. Data analysis in this research use descriptive statistic with percentage technique. The results showed that 50.9% of students had high academic self-concept, and the remaining 49.1% of students had low academic self-concept. Students with low academic self-concept have average grades below 146.3. The results of this study are useful for lecturers, and college counselors as a consideration to facilitate students in developing positive academic self-concept.